2016
DOI: 10.2147/ijn.s108152
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal effects of laser-activated surface plasmonic gold nanoparticles on the apoptosis and osteogenesis of osteoblast-like cells

Abstract: The specific properties of gold nanoparticles (AuNPs) make them a novel class of photothermal agents that can induce cancer cell damage and even death through the conversion of optical energy to thermal energy. Most relevant studies have focused on increasing the precision of cell targeting, improving the efficacy of energy transfer, and exploring additional functions. Nevertheless, most cells can uptake nanosized particles through nonspecific endocytosis; therefore, before hyperthermia via AuNPs can be applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In this context, C-CPE could be a tool in cancer therapy with less side-effects compared to the original CPE. The technique could be a complement or an alternative to antibodies functionalized AuNPs 14 , 53 55 .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, C-CPE could be a tool in cancer therapy with less side-effects compared to the original CPE. The technique could be a complement or an alternative to antibodies functionalized AuNPs 14 , 53 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus is a key component of mineral crystals, and hyperthermia can promote the biomineralization process 2531,33 . With the special capability to provide phosphate and hyperthermia, the Apt-bioinspired MVs were further studied for biomineralization purposes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, ultrasmall BP nanosheets with sizes of several nanometers (usually named as BP quantum dots, BPQDs) have high photothermal conversion efficiency and thus can be used as a promising photothermal agent 24 . Previous researches have indicated that hyperthermia promotes biomineralization by stimulating the up-regulated expression of proteins, including alkaline phosphatase (ALP) and heat shock proteins (HSP) 2529 , thus increasing the generation of mineral crystals and realizing bone reconstruction 2931 . These special properties render BPQDs promising biomaterials for stimulating biomineralization and further promoting mineralization-guided biological behavior regulation and medical engineering.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of cells with AuNPs, loss of cell viability may be due to localized heat at the membrane, destabilizing the lipid bilayer, and permeabilizing it 26 . Also, endoskeleton damage is likely to happen, since it is where AuNPs are mostly located at 4 h 27 . It is possible to observe that HCT116 DOXR are more sensitive to AuNPs’ irradiation than HCT116, since at 90 s irradiation the difference in cell death of irradiating or not HCT116 DOXR is 91% compared with 66% for HCT116 (Fig.…”
Section: Resultsmentioning
confidence: 99%